Toward an Integrated European Economic System: An Assessment of regional integration and specialization - Andreas P. Cornett (European Regional Science Association (ERSA), 2001)
The purpose of this paper is to provide a tentative record of the process of integration between the EU and the East and Central European economies. Twelve years after the break up of the former state trade system in Eastern Europe, a new international system of production and trade is visible. The first transition countries are on the edge of becoming members of the EU. After a brief examination of the state of the `pre-accession' with regard to trade, FDI and the adaptation to the economic regime of market economies the nature of economic links between the EU and the CEEC is analyzed. Point of departure is a survey of the political and institutional framework for economic transactions established during the decade. Based on this overview the main focus is on the issue of the participation of the former state trade economies in the regional production system in Europe. The first step is an overall assessment of economic links (i.e. trade and FDI) within the region and between the involved countries and the outside world. Secondly, an in-depth analysis of trade and specialization is added, mainly through an outline of intra-industry trade between the EU and the former transition economies. The third step of the investigation concentrates on a case study of a particular sector (textile and apparel) to illuminate impacts of integration not only in the transition economies, but also in the EU countries. The final section of the paper offers the findings and an assessment of the level of integration within the region. The latter is based on theoretical concepts of economic integration. Finally a number of scenarios for the future trends of development in the economic relations between the CEEC and the EU are sketched, in particular with regard to impacts on regional and international competitiveness. Key words: A new system of production - specialization - trade - FDI - regional integration- competitiveness.
Keywords: 330